2008
DOI: 10.1099/mic.0.2007/016337-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and symbiotic significance of nodulation outer proteins secretion in Sinorhizobium fredii HH103

Abstract: In this work we show that the Sinorhizobium fredii HH103 ttsI gene is essential for the expression of the tts genes and secretion of nodulation outer proteins (Nops). Moreover, we demonstrate for the first time, to our knowledge, that the nod box preceding ttsI is necessary for Nops secretion. TtsI is responsible for the transcriptional activation of nopX, nopA, rhcJ and rhcQ. We confirm that the S. fredii HH103 ttsI gene is activated by NodD1 and repressed by NolR. In contrast, NodD2 is not involved in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 39 publications
4
92
0
Order By: Relevance
“…The shift in position of Gln56 in each half-site of the oligo AT DNA, either to interact with A2 in the first site or away from T7' in the second site, suggested that movement of this residue may play a role in the previously observed recognition by NolR of variable operator sites (17)(18)(19)(20)(21)(22)(23)(24). To examine the possible role of Gln56 as a conformational switch in DNA binding, NolR was crystallized with oligo AA DNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The shift in position of Gln56 in each half-site of the oligo AT DNA, either to interact with A2 in the first site or away from T7' in the second site, suggested that movement of this residue may play a role in the previously observed recognition by NolR of variable operator sites (17)(18)(19)(20)(21)(22)(23)(24). To examine the possible role of Gln56 as a conformational switch in DNA binding, NolR was crystallized with oligo AA DNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1-3) more accurately define the interaction sequences in each asymmetric half site as ATTAG on the 5′ strand and CTTC on the 3′ strand. A remarkable feature of NolR is that the homodimer binds to an asymmetric operator site with variable sequences at two positions, one in each half site, which allows versatility in recognition of NolR operator sites of multiple target genes (19,20,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations